Honeycomb‐like hierarchical porous silicon composites with dual protection for ultrastable Li‐ion battery anodes. (2nd September 2021) - Peng, Xudong; Xiong, Cheng; Lin, Yanke; Zhao, Chen; Zhao, Tianshou
Abstract: Silicon offers a high theoretical specific capacity for anodic lithium storage. However, its applications are hindered by the electrode instability caused by the sharp volume change, and the limited rate performance resulted from the insulating property. Herein, we introduce a facile and fast method of preparing honeycomb‐like silicon‐based anodes (MXene‐Si@C) with porous structure using MXene and carbon‐coated silicon. The dual protection from both the surface coating and as‐formed interlayered vacant spaces ameliorate the volume expansion of the silicon and thus reinforce the mechanical stability of the electrode. In addition, the highly conducting MXene and the surface carbon coating form a hierarchical and consecutive electron‐conducting network with evidently reduced resistance. With this proposed composite, a high average Coulombic efficiency of 99.73% and high capacity retention of 82.4% after 300 cycles at 1 A/g can be achieved even with an areal loading around 1.5 mg/cm 2 . Coupled with an NCM523 cathode, the proof‐of‐concept full cell delivers a high capacity of 164.2 mAh/g with an extremely high energy density of 574 Wh/kg (based on the mass of the electrode materials) at 0.2 C and an excellent cyclability at 0.5 C of 100 cycles with decent capacity retention (80.28%). Abstract : Silicon anodes usually suffer a short lifespan due to the sharp volume change. Herein, a comprehensive and efficient method is provided to acquire a hierarchical structure with dual protection on the Si particles, which enables ultrastable long‐term cycling stability and practical feasibility in the full batteries.